Faktor-Faktor yang Membahagiakan Relawan Muslim di Organisasi Nirlaba Berbasis Islam - Faletehan, Aun; Zuhri , Syaifudin (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2024)
This article investigates the factors contributing to the happiness of Muslim volunteers in nonprofit organizations. Employing a qualitative phenomenological approach, the study conducts a multi-case investigation in two religious-based nonprofit organizations in Surabaya, Indonesia, conducting 24 in-depth interviews with senior volunteers. Findings reveal that familial culture, religious culture, personal development, nonprofit leadership, and rewards play significant roles in fostering volunteer happiness. Additionally, the article provides theoretical contributions to the volunteer motivation literature and practical insights for nonprofit organization managers to enhance volunteer experience quality and program effectiveness.